Effectiveness of complex exercise programs to promote growth in children undergoing growth hormone therapy - Lee, Jeong-Hoon; An, Chang-Sik; Yu, Won-Jong; Lee, Chang-Ryeol; Kim, Jeong-Lae (Edelweiss Applied Science and Technology, 2025)
This study was conducted to evaluate the effectiveness of a complex exercise program designed to promote growth in children receiving growth hormone therapy. A total of 24 participants were divided into two groups: 12 in the experimental group and 12 in the control group. Both groups received growth hormone injections, with the experimental group additionally participating in a complex exercise program, while the control group only received the injections. Growth hormone therapy consisted of injections once daily, six days a week. The complex exercise program was administered under the supervision of a physical therapist, three times a week for 30 minutes per session, over a period of 12 weeks. Height, leg length, weight, and BMI were measured before and after the intervention and compared between the groups. The results showed that the experimental group, which combined growth hormone therapy with the exercise program, experienced greater growth promotion. This suggests that the complex exercise program has a positive effect on growth in children with short stature and could be an effective component in developing programs to promote growth.